2015
DOI: 10.1039/c5ra05725f
|View full text |Cite
|
Sign up to set email alerts
|

N-doped mesoporous carbon nanosheets obtained by pyrolysis of a chitosan–melamine mixture for the oxygen reduction reaction in alkaline media

Abstract: Simple thermal decomposition of low-cost precursors in an inert atmosphere leads to mesoporous nitrogen-doped carbon nanosheets with electrocatalytic activity towards ORR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 57 publications
2
62
0
1
Order By: Relevance
“…,60,61,82,83,84 however, to our knowledge no such comparative study on oxygen reduction behaviour on CM-and DCDA-derived NCNTs has been reported as yet. Similar tendency has been reported by Rybarczyk et al recently 85. The LSV behaviour of the ORR on the NCNT-CM and NCNT-DCDA catalysts is shown inFigures 8a and 8b, respectively.…”
supporting
confidence: 88%
“…,60,61,82,83,84 however, to our knowledge no such comparative study on oxygen reduction behaviour on CM-and DCDA-derived NCNTs has been reported as yet. Similar tendency has been reported by Rybarczyk et al recently 85. The LSV behaviour of the ORR on the NCNT-CM and NCNT-DCDA catalysts is shown inFigures 8a and 8b, respectively.…”
supporting
confidence: 88%
“…[118] Figure 14d shows an expanded interlayer spacing of about 0.359 nm. [118] Figure 14d shows an expanded interlayer spacing of about 0.359 nm.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[132][133][134] Basing on this point, Wan et al prepared TiS 2 intercalated by organic polymer, which demonstrated an electrical conductivity of 790 S cm −1 and a power factor of 0.45 mW m −1 K −2 . [118] Copyright 2015, Royal Society of Chemistry. a) TEM image of NG-NiCo.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The NG film tended to agglomerate into a bulk graphite layer with a decreasing GO to melamine ratio. During the doping process of GO with melamine, melamine was decomposed into other nitrogen species such as carbon nitride, cyanamide and melem with the release of ammonia gas at elevated temperature [21,22]. Decreasing the ratio of GO to melamine yielded higher amounts of these condensed nitrogen species, with the evolution of a large excess of ammonia gas.…”
Section: Physical Characterizationmentioning
confidence: 99%